2018
DOI: 10.5194/acp-2018-1021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ice nucleation activity of silicates and aluminosilicates in pure water and aqueous solutions. Part 3 – Aluminosilicates

Abstract: <p><strong>Abstract.</strong> Aluminosilicates (such as feldspars, clay minerals and micas) and quartz (a crystalline form of silica), constitute the majority of airborne mineral dust. Despite similarities in structures and surfaces they differ greatly in terms of their ice nucleation (IN) efficiency. Here, we show that determining factors for their IN activity include surface ion exchange, NH<sub>3</sub> or NH<sub>4</su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 124 publications
2
18
0
Order By: Relevance
“…Furthermore, in Part 3 (Kumar et al, 2018b) we show that micas (muscovite and biotite) and gibbsite, which reveal no IN activity in pure water emulsion freezing experiments, develop a heterogeneous freezing signal in the presence of NH3 and (NH4)2SO4. We therefore tested the amorphous silica samples for a similar effect.…”
Section: Dependence Of the Heterogeneously Frozen Fraction On The Prementioning
confidence: 79%
See 4 more Smart Citations
“…Furthermore, in Part 3 (Kumar et al, 2018b) we show that micas (muscovite and biotite) and gibbsite, which reveal no IN activity in pure water emulsion freezing experiments, develop a heterogeneous freezing signal in the presence of NH3 and (NH4)2SO4. We therefore tested the amorphous silica samples for a similar effect.…”
Section: Dependence Of the Heterogeneously Frozen Fraction On The Prementioning
confidence: 79%
“…In Part I of this series, we showed that heterogeneous freezing onsets of microcline showed strong deviations from the wateractivity-based description to higher freezing temperatures from predicted values when suspended in dilute NH3/NH 4 + containing solutions and substantial decrease in IN efficiency in more concentrated solutions of inorganic salts including NH 4 + containing salts and NH3 (Kumar et al, 2018a). In Kumar et al (2018b) we extended this investigation to other aluminosilicates and found that an increase of Thet in the presence of NH 4 + containing solutes is a general feature of feldspars, clay minerals and micas, while the decrease in IN efficiency at higher solute concentration is a more specific characteristic of K-feldspars and most pronounced for microcline. Conversely, SA quartz follows quite well the water-activity-based prediction of Thet in case of pH neutral suspensions.…”
Section: Heterogeneous In Of Quartz In Aqueous Solutionsmentioning
confidence: 88%
See 3 more Smart Citations